2001
DOI: 10.1634/theoncologist.6-suppl_3-17
|View full text |Cite
|
Sign up to set email alerts
|

Nonanthracycline Containing Docetaxel-Based Combinations in Metastatic Breast Cancer

Abstract: Many active nonanthracycline-containing regimens are emerging from clinical trials and may offer the option of treating metastatic breast cancer without resorting to doxorubicin or analogues. When used first-line in metastatic breast cancer, both cisplatin and carboplatin are active agents and hence candidates for combination therapy. In a dose-finding study in patients with no prior chemotherapy for metastatic disease, docetaxel administered together with cisplatin produced a promising response rate (RR) of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…While both agents are widely used for the treatment of non-inflammatory and inflammatory breast cancer [22,23], the majority of patients develop resistance to the drugs, particularly after a previous round of chemotherapy [24]. Of the genes comprising the genetic signatures of resistance, we found that the significant majority were drug-specific and code for proteins involved in drug transport, drug metabolism, growth, survival, and cell death control.…”
Section: Introductionmentioning
confidence: 85%
“…While both agents are widely used for the treatment of non-inflammatory and inflammatory breast cancer [22,23], the majority of patients develop resistance to the drugs, particularly after a previous round of chemotherapy [24]. Of the genes comprising the genetic signatures of resistance, we found that the significant majority were drug-specific and code for proteins involved in drug transport, drug metabolism, growth, survival, and cell death control.…”
Section: Introductionmentioning
confidence: 85%
“…The widespread use of anthracycline-based chemotherapy in the adjuvant treatment of breast cancer has contributed to an increasing number of patients presenting with MBC resistant to this class of drugs. The majority of anthracycline-naïve patients with MBC are treated with anthracyclines as first-line therapy for metastatic disease [2,3]. The taxanes are also considered to be highly active agents in the treatment of breast cancer, with single-agent docetaxel showing response rates up to 49-57% in anthracycline-pretreated patients, confirming the lack of complete cross-resistance between these classes of agents [4,5].…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, the majority of anthracycline-naïve patients with ABC are treated with anthracyclines as first-line therapy for metastatic disease [2]. Thus, there is a need to develop effective non-anthracycline-containing regimens, since the use of anthracycline salvage chemotherapy is limited due to the development of drug resistance [3]. The taxanes are also considered to be highly active agents in the treatment of breast cancer, with single-agent docetaxel showing response rates (RR) up to 49–57% in anthracycline-pretreated patients, confirming the lack of complete cross-resistance between these classes of agents [4,5].…”
Section: Introductionmentioning
confidence: 99%